A agricultura convencional e a agricultura sintrópica: uma discussão inicial - Matsumura, Edson Satio [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This study aimed to analyze the conventional agriculture and to introduce the syntropic agriculture as na alternative model, it also aimed to investigate aspects that fits the conventional agriculture in the dimension of entropy; and to comprehend the concepts of syntropy applied to the agriculture. Thus, it was used the bibliographic research by surveying the theoretical framework regarding agriculture, biophysics and syntropy. Finally, through this study it could be understood that the unsustainability that the conventional farming shows to have as an element can be analyzed by its entropic aspects and reveals a reductionist understanding of agriculture. Prioritizing the amount produced over the quality of its products and of its social and environmental results. On the other hand, the syntropic agriculture, being designed by Ernst Götsch, is presented as an alternative to reconciliate human activities to enegetic increases in the systems. Allowing a new way to understand the entropic processes and its functions to life

O trabalho objetivou discutir a agricultura convencional e apresentar a agricultura sintrópica como uma forma agrícola alternativa, bem como averiguar aspectos que enquadram a agricultura convencional na dimensão entrópica; e compreender a sintropia aplicada à agricultura. Para tanto, foi utilizado como método a pesquisa bibliográfica, através do levantamento do referencial teórico à respeito da agricultura, biofísica e sintropia. Enfim, através desse estudo pôde-se compreender que a insustentabilidade que a agricultura convencional demonstra ter como característica pode ser analisada por seus aspectos entrópicos e revela uma compreensão reducionista da agricultura. Priorizando a quantidade produzida em detrimento a qualidade de seus produtos e dos resultados ambientais e sociais de seus processos. Por outro lado, apresenta-se a agricultura sintrópica, de Ernst Götsch, como uma tentativa de reconciliamento das atividades humanas com o aumento energético nos sistemas. Fornecendo uma nova maneira de compreender os processos entrópicos e suas funções perante a vida
Keywords: Agricultura; Entropia; Pesquisa bibliografica; Biofísica